International women's magazines in Korea : the relationship with transnational advertising - Oh, Hyun Sook (2010)
In this research, I have attempted to provide an analysis of the context, the produciton and the content of international women's magazines in Korea. International women's magazines have been approached as a significant site for exploring the dynamic interaction between global and local forces. Thus, my study investigated how the interaction of the global and local forces is involved in the production of international woman's magazines in the specific context and how that dynamic interaction influences the content of the magazines.